Processing Eruca sativa leaves in the nanoscale and study its effectiveness for removing Cibacron red dye from their aqueous solutions - Mahdi Rheima, Ahmed; Khanjar, Aya Qasim Khanjar; Farhan, Ahlam Mohammed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The discharge of dyes into the water is a significant source of pollution, which is especially concerning given that textile mills are the primary contributor. Nanomaterial-based solutions to this issue have required extensive research and investigation due to their complex nature. In this research, novel nanoparticle were successfully synthesized using the leaves of the Eruca sativa plant. The nano was analyzed using scanning and transmission electron microscopy (SEM and TEM) measurements, and their crystal structure was determined using the X-ray diffraction technique (XRD). The incorporation of NPs resulted in an increase in the uptake of the Cibacron red dye. At a contact time of 30 minutes, observed a faster adsorption onto ES. In the process of describing the adsorption process, the Langmuir model (R2 =0.9817) and the pseudo-second-order model (R2 = 0.9884) were the most appropriate models to use. An investigation into thermodynamics was carried out in order to arrive at the following values for the parameters of G, H, and S: -1.173 kJ/mol, 16.794 J/mol K and 56.05 J/mol. In conclusion, the novel nano that was synthesized is an excellent adsorbate surface for the Cibacron- red dye.